O ensino de magnetismo nos anos iniciais: uma análise dos livros didáticos aprovados no PNLD 2013 - Leão Júnior, Ilson Barboza (2015)
The Science textbooks are the most used textbooks, if not the only, by teachers and students in Brazilian schools. Bittencourt (1997), Leite et. al. (2006) and Lorenz (1986) show the importance of this teaching resource in schools. This paper analyzes the teaching collections approved in PNLD 2013 - early years, which address the concepts of magnetism and their practical activities. The first section presents a historical evolution of the teaching of science, based on Krasilchik (1987), and the main methodological trends of the area. In the second section, the historicity of the textbook of Sciences, the textbook of Sciences and the National Textbook Program (PNLD) and a literature review, the main journals in the field, on the textbook of Sciences with the physical knowledge magnetism. In the third section we report the importance of addressing the concepts of magnetism, underpinned by the National Curriculum Parameters of Basic Natural Science Education (PCNEF) and the National Curriculum Guidelines for Primary Schools (DCNEF). Use in our research content analysis (CA) Bardin (1979) , applied to 13 teaching collections of constant Sciences in the textbook guide, its aspects relating to content and the experimental activities of magnetism. In the fourth section, we present an educational product as an article, to help teachers in the early years, the state and municipal networks, to guide the Science textbooks, as well as suggestions of the main practical activities with magnetism theme. s a result , it was found that magnetism content is present in most teaching collections of Sciences, mainly magnetic phenomena that can be viewed and manipulated by children. In relation to magnetism of practical activities found in the textbook collections, it was found that there were no activities of the “demonstration”, few of the “illustrative” and “investigative" and mostly in the form of descriptive experiments, showing thus the scientific method. In the appendices present a table showing the practical activities in the teaching collections and in the form of educational product , an article, to help teachers in the early years , the state and municipal public networks, with guidance on the Science textbooks , as well as suggestions of main practical activities with magnetism theme.